2021
DOI: 10.1016/j.tranon.2021.101145
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of androgen receptor splicing variant 7 (AR-V7) expression in patients with castration resistant prostate cancer: A systematic review and meta‐analysis

Abstract: Highlights Studies have shown that AR-V7 may be correlated with the poor prognosis of castration resistant prostate cancer (CRPC), however, clinicopathological characteristics of AR-V7 have not been fully elucidated. We enrolled 24 studies with 2307 eligible patients for a systemic review and meta-analysis. AR-V7 positivity was associated with higher Gleason score, bone or any site metastasis, presence of pain and worse ECOG performance score in CRPC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Treatment options for patients with CRPC are severely limited [ 5 , 37 , 39 ], and constitutively active AR splice variants, especially AR-v7, pose a significant challenge [ 52 ]. Our in vitro findings suggested that the above two orally available pharmaceutical agents may pre-sensitize CRPC cells and enhance the tumor-eliminating ability of FUS by suppressing crucial pro-survival signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for patients with CRPC are severely limited [ 5 , 37 , 39 ], and constitutively active AR splice variants, especially AR-v7, pose a significant challenge [ 52 ]. Our in vitro findings suggested that the above two orally available pharmaceutical agents may pre-sensitize CRPC cells and enhance the tumor-eliminating ability of FUS by suppressing crucial pro-survival signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro findings suggested that the above two orally available pharmaceutical agents may pre-sensitize CRPC cells and enhance the tumor-eliminating ability of FUS by suppressing crucial pro-survival signaling pathways. In addition to AR, both NF-κB and Akt signaling pathways play central roles in CRPC cell proliferation and metastasis, via pro-inflammatory signaling, and production of cytokines, chemokines and adhesion molecules [ 35 , 52 , 53 ]. In the absence of androgen, CRPC cells rely on these alternative pro-survival mechanisms to maintain their uncontrolled proliferation and metastatic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, knockdown of YAP1 and PAK2 both reduced cell colony formation and cell invasion activity also suggested an important factor in CRPC invasion (19). Similarly, AR-V7 positivity associated with a higher bone, or any site, metastasis in CRPC (16). Moreover, knockdown of EpCAM contributed to reduced invasion in PC-3, DU145, and C4-2B cells (32).…”
Section: Crpc Invasion and Metastasismentioning
confidence: 94%
“…The most well-described AR-V is still AR-V7. In CRPC, a recent meta-analysis revealed that AR-V7-positive is linked to greater ECOG performance, metastatic spread, higher Gleason scores, and worse pain management [ 62 ].…”
Section: Molecular Events On Resistance Mechanisms To Ar Signaling Pa...mentioning
confidence: 99%